Inspiratory muscle strength is a determinant of maximum oxygen consumption in chronic heart failure. Issue 4 (October 1995) - Chua, T. P.; Anker, S. D.; Harrington, D.; Coats, A. J.
Abstract : OBJECTIVE--To investigate the significance of respiratory muscle weakness in chronic heart failure and its relation both to maximum oxygen consumption during cardiopulmonary exercise testing and to skeletal muscle (quadriceps) strength. SUBJECTS--Seven healthy men aged 54.9 (SEM 4.3) years and 20 men with chronic heart failure aged 61.4 (1.6) years (P = 0.20) with radionuclide left ventricular ejection fraction of 25.4 (3.0)%. METHODS--Mouth pressures during maximum static inspiratory effort (PImax) at functional residual capacity (FRC) and residual volume (RV) were measured in all subjects and taken as indices of inspiratory muscle strength. Similarly, mouth pressures during maximum static expiratory effort (PEmax) at FRC and total lung capacity (TLC) were taken as indices of expiratory muscle strength. Cardiopulmonary exercise testing was performed in all subjects. All controls and 15 heart failure patients also had their right quadriceps muscle strength measured. RESULTS--There was respiratory muscle weakness in heart failure patients, with reduction of PImax at FRC (59.7) (6.3) v 85.6 (9.6) cm H2O, P = 0.045), PEmax at FRC (94.8 (6.2) v 134.6 (9.1) cm H2O, P = 0.004), and PEmax at TLC (121.7 (8.5) v 160.7 (13) cm H2O, P = 0.028). PImax at RV was also reduced but this did not reach statistical significance (77.3 (6.6) v 89.3 (13) cm H2O, P = 0.44). There was also significant weakness of the right quadriceps muscle (308.5 (22) v 446.2 (28) N, P = 0.001). PImax at both FRC and RV correlated with maximum oxygen consumption (r = 0.59, P = 0.006, and r = 0.45, P = 0.048 respectively) but not PEmax. There was, however, no significant correlation between PImax and right quadriceps strength. CONCLUSIONS--Respiratory muscle weakness is seen in chronic heart failure. The results suggest that inspiratory muscles are important in determining maximum oxygen consumption and exercise tolerance in these patients. The lack of correlation between respiratory and right quadriceps muscle strength further suggests that the magnitude and time course of respiratory and locomotor muscle weakness may differ in individual patients. Treatment aimed at improving the function of the involved muscle groups may alleviate symptoms.